The Role of Metabolic Syndrome in Endometrial Cancer: A Review - Yang, Xiao; Wang, Jianliu (Frontiers in Oncology, 2019)
Endometrial cancer is one of the most common cancers of the female reproductive system. Although surgery, radiotherapy, chemotherapy and hormone therapy can significantly improve the survival of patients, the treatment of patients with very early lesions and a strong desire to retain reproductive function or late recurrence is still in the early stages. Metabolic syndrome (MS) is a clustering of at least three of the five following medical conditions: central obesity, high blood pressure, high blood sugar, high serum triglycerides, and low serum high-density lipoprotein (HDL). Obesity, diabetes and hypertension often coexist in patients with endometrial cancer, which increases the risk of endometrial cancer, also known as the "triple syndrome of endometrial cancer". In recent years, epidemiological and clinical studies have found that MS associated with metabolic diseases is closely related to the incidence of endometrial cancer. However, the key molecular mechanisms underlying the induction of endometrial cancer by MS have not been elucidated to date. Characterizing the tumor metabolism microenvironment will be advantageous for achieving a comprehensive view of the molecular mechanism of metabolic syndrome associated with endometrial cancer and for providing a new target for the treatment of endometrial cancer. This review focuses on recent advances in determining the role of metabolic syndrome-related factors and mechanisms in the pathogenesis of endometrial cancer. We suggest that interfering with the tumor metabolic microenvironment-related molecular signals may inhibit the occurrence of endometrial cancer.